Hubungan Persepsi Penyakit dan Lama Menderita dengan Manajemen Diri Pada Pasien Dengan Diabetes Mellitus Tipe 2 - Salsabilla, Ghina; Mailani, Fitri; Oktarina, Elvi (Universitas Fort De Kock Bukittinggi, 2023)
Background: The high incidence of type 2 diabetes mellitus and its complications, as well as an unhealthy lifestyle, cannot be separated from the problem of low self-management behavior in patients with diabetes mellitus. Chronic disease for a long time tends to affect the perception of disease and duration of suffering in patients with diabetes mellitus. The purpose of this study was to determine the relationship between perception of disease and length of suffering with self-management in type 2 diabetes mellitus at Crocodile Health Center Lubuk Padang City. Methods: is a quantitative study with a correlational design and a cross sectional approach. The sample of this research was 70 respondents who were taken using purposive sampling technique. Data collection used the SDSCA-Revised and B-IPQ questionnaires. Data analysis using the Pearson Product test. Results: showed that the average perception of disease was 34.04, the average length of suffering was 6.00 years, the average self-management of diabetes mellitus patients was 41.91.There is a relationship between perception of disease and self-management of diabetes mellitus patients with p value = 0.000. There is a significant relationship between duration of suffering and self-management of diabetes mellitus patients with p value = 0.040. Conclusion: This research gain the increasing of self-management activities on the intensity of PROLANIS activities, especially providing diabetes mellitus exercises from 1x a month to 2-3x a month, conducting regular home visits to help elderly patients check their blood sugar levels, providing comprehensive education, mentoring and monitoring drug consumption.Keywords: type 2 diabetes mellitus, illness perception, illness duration, self-management